A Bibliometric Analysis and Systematic Review on Financial Literacy, Brand Shopee, Bisnis Online and E-Marketplace - Kurniawan, Kurniawan (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This research aims to discover how Shopee compares its products to grow a new economy in the digital era. The article's writing uses a qualitative analysis method through a literature study with data collection techniques using a database cited Scopus Self-managed remote access. The "co-occurrence" data type uses the "full counting" method, which is then carried out using "bibliometrics" in "VOSviewer" software based on descriptive metadata, identifying or describing title and abstract elements with the keyword shopee for the 2015-2024 period. There are 121 articles, which are then analyzed using descriptive analysis. The research results show that publications about Shopee have increased. Indonesia, with the highest production on this subject, stands out as the country with the most publications on all the analyzed topics, followed by other countries. Most articles' primary areas of study are computer science, decision-making, business, management and accounting, social science engineering, and mathematics. In this field of study, identifying the main concepts related to it shows that Shopee's financial literacy branding has a management system that can improve strategy and competitiveness in growing the new economy in the digital era. Economic growth in electronic markets stands out due to the emergence of digital platforms that will enhance conditions for buyers and sellers, with digital marketing and sales focused on promoting and commercializing products in electronic markets.